HUMOR DALAM MASYARAKAT MEDAN - Agus Mulia (Balai Bahasa Sumatera Utara, 2019)
In Indonesia, humour is one of genres in spoken literature but also becomes part of the society arts, like ludruk, ketoprak, lenong, reog, calung, makyong, wayang kulit (leater puppet), wayang golek (woaden puppet), etc. Humour in arts group becomes supporting element, even becomes main element of appeal. Humor in other term called comedy, banyolan, dagelan also exists in the society and is used by many tribes in north Sumatera, especially in Medan City. There are many kinds of humour in Medan due to the variations of tribes develops own its own spoken humour.